POTENTIAL OF ENCAPSULATION Bacillus cereus BTH-22 AGAINTS BACTERIAL WILT DISEASE ON EGGPLANT: - - Purnawati, Arika; Triwahyu P, Endang; Fari A, Haidar (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Endophytic bacteria are a group of bacteria that live in plant tissues, potentially as biological agents of plant diseases, especially wilt disease caused by Ralstonia solanacearum and as an inducer of eggplant (Solanum melongena) plant growth. One of these bacteria is Bacillus cereus BTH-22 which was isolated from healthy eggplant stems in Kediri. The purpose and formulation of the problem are to obtain an encapsulation formulation of B. cereus BTH-22 which has the potential as a biological agent against wilt disease caused by R. solanacearum and as an inducer of eggplant (S. melongena) plant growth. The novelty of the research is the encapsulation formulation of B. cereus which is applied to eggplant plants with wilt, because the application generally uses root soaking, watering to the soil surface, mixing with fertilizer, liquid and powder formulations but all are easily washed away by rain. The research method is as follows: (1) Making encapsulation formulation: 75% Na-alginate with 10% aloe vera extract (Na-1) and 75% Na-alginate, 0.875% zeolite and 0.875% sago flour (Na-2), (2) Sterile soil, inoculate R. solanacearum and prepare 1 month old plants, (3) Application of encapsulation formulation was carried out 3 days after inoculation of R. solanacearum (107CFU/mL) using a Completely Randomized Design with 3 replications. Observations were made on days 7, 14, 21, 28, 35, 42, 49 including : disease intensity, plant height, number of leaves, number of flowers. The results of the study showed: viability in the Na-1 and Na-2 treatments was higher than control at the 48th to 96th hours, disease intensity in the Na-1 and Na-2 treatments was lower than control at the 7th to 49th day, plant height in the Na-1 and Na-2 treatments was higher than control at the 14th to 49th day.